IMPLEMENTASI PENINGKATAN KUALITAS PERMUKIMAN DAN MASYARAKAT DI KAMPUNG AKUARIUM, KELURAHAN PENJARINGAN, JAKARTA UTARA - Shafira Fadhliana M.; Herbasuki Nurcahyanto; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The existence of slum area in DKI Jakarta cannot be avoided from the urbanization that occurs. The increase in population has resulted in the need for land for housing to increase, as a result, many people have set up settlements on lands that they feel can be used as houses even though they do not have enough land. Most houses that stand in slums do not pay attention to the quality of the building, in the sense that they do not pay attention to lighting, area of residential roads, ventilation, etc. Therefore, to organize settlements in DKI Jakarta, Keputusan Gubernur Nomor 878 Tahun 2018 and Peraturan Gubernur Nomor 90 Tahun 2018 were issued to organize settlements while improving the quality of the community.This study aims to analyze the implementation of improving the quality of settlements and communities and analyze the driving and inhibiting factors in its implementation in Kampung Akuarium, North Jakarta. The research method used in this research is descriptive qualitative using primary data sources obtained through in-depth interviews and field observations as well as secondary data. In this study, researchers analyzed the implementation of improving the quality of settlements through the stages of implementation, namely the community action plan, the development of physical, social, and economic aspects, and the monitoring and evaluation stage. In this study, it was found that the stages of the community action plan had been carried out in accordance with the directions given, although there were obstacles in collaborating with the community, meanwhile until now the construction of the Kampung Susun Aquarium was still being carried out. The development of the physical aspect has been carried out according to the directions but in improving the quality of the community in the socio-cultural and economic aspects it has not been fully implemented. In the implementation of this program there are driving factors, communication, disposition, and bureaucratic structure as well as inhibiting factors, resources